Financial Ratio Analysis of Local Government of Pematang Siantar City - Sri Martina; Wico Jontarudi Tarigan (Jurnal Minfo Polgan, 2023)
This study aims to determine the financial performance of the Regional Government of Pematang Siantar City when viewed from eight ratios such as regional financial independence ratio, fiscal decentralization ratio, regional financial dependence ratio, PAD effectiveness ratio, PAD efficiency ratio, growth ratio, expenditure compatibility ratio and solvency ratio. This type of research is quantitative with descriptive methods. The data used is the 2022 Pematang Siantar City Regional Government Budget Realization report. The data analysis used is a quantitative descriptive method using financial ratios. Looking at the results of the analysis of the eight ratios, there are three of them categorized as unfavorable, namely the level of regional financial independence which is still very low, the Fiscal Decentralization Ratio is still not good and the level of Regional Financial Dependence is still high. While the other ratio is said to be good. This research still has many shortcomings, therefore the author provides suggestions to be a reference for future researchers in the same location or program as the Pematang Siantar City Regional Government program to Measure the Financial Performance of the Regional Government of Pematang Siantar City, North Sumatra Province